Snort Cookbook - Babbin, Jacob (O'Reilly, 2011)
If you are a network administrator, you're under a lot of pressure to ensure that mission-critical systems are completely safe from malicious code, buffer overflows, stealth port scans, SMB probes, OS fingerprinting attempts, CGI attacks, and other network intruders. Designing a reliable way to detect intruders before they get in is an essential--but often overwhelming--challenge. Snort, the defacto open source standard of intrusion detection tools, is capable of performing real-time traffic analysis and packet logging on IP network. It can perform protocol analysis, content searching, and matching. Snort can save countless headaches; the new Snort Cookbook will save countless hours of sifting through dubious online advice or wordy tutorials in order to leverage the full power of SNORT. Each recipe in the popular and practical problem-solution-discussion O'Reilly cookbook format contains a clear and thorough description of the problem, a concise but complete discussion of a solution, and real-world examples that illustrate that solution. The Snort Cookbook covers important issues that sys admins and security pros will us everyday, such as: installation optimization logging alerting rules and signatures detecting viruses countermeasures detecting common attacks administration honeypots log analysis But the Snort Cookbook offers far more than quick cut-and-paste solutions to frustrating security issues.